2013
DOI: 10.1016/j.molcel.2013.08.017
|View full text |Cite
|
Sign up to set email alerts
|

Circular Intronic Long Noncoding RNAs

Abstract: We describe the identification and characterization of circular intronic long noncoding RNAs in human cells, which accumulate owing to a failure in debranching. The formation of such circular intronic RNAs (ciRNAs) can be recapitulated using expression vectors, and their processing depends on a consensus motif containing a 7 nt GU-rich element near the 5' splice site and an 11 nt C-rich element close to the branchpoint site. In addition, we show that ciRNAs are abundant in the nucleus and have little enrichmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

21
1,936
6
15

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,933 publications
(2,044 citation statements)
references
References 54 publications
21
1,936
6
15
Order By: Relevance
“…4D). Cytosine branchpoints have been shown to be resistant to debranching (Hornig et al 1986) and may comprise a distinct subset recently associated with stable lariat and long noncoding RNA formation (Zhang et al 2013).…”
Section: Branchpoint Featuresmentioning
confidence: 99%
“…4D). Cytosine branchpoints have been shown to be resistant to debranching (Hornig et al 1986) and may comprise a distinct subset recently associated with stable lariat and long noncoding RNA formation (Zhang et al 2013).…”
Section: Branchpoint Featuresmentioning
confidence: 99%
“…Indeed, recent studies have revealed that circRNAs are differentially expressed in different human cell lines and tissues, serve as regulators of transcription and protein expression and can act as miRNA sponges. [4][5][6][7] Several different types of RNA circles originating from diverse cellular processes have been identified. Most eukaryotic circRNAs result from splicing reactions that are catalyzed either by the spliceosome or ribozymes corresponding to Group I and Group II introns.…”
Section: Introductionmentioning
confidence: 99%
“…The size distributions of the high‐quality reads were varied from 18 to 28 nts in our library and the peak was at the 25 nt , which was on par with previous studies (Ge et al., 2013; Liang, Feng, Zhou, & Gao, 2013; Sattar et al., 2012). Our study indicated the unique read distributes of 26–28 nts with a relative lower abundance, which is common in many small RNA libraries (Chang et al., 2016; Jagadeeswaran et al., 2010; Surridge et al., 2011; Zhang et al., 2013), indicating the presence of piRNAs. Piwi RNAs (piRNAs) are the class of small RNAs mediating chromatin modifications (Ross, Weiner, & Lin, 2014) which are derived mainly from retrotransposons and other repetitive elements with high sequence diversity (Ross et al., 2014; Siomi, Sato, Pezic, & Aravin, 2011; Zhang et al., 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Our study indicated the unique read distributes of 26–28 nts with a relative lower abundance, which is common in many small RNA libraries (Chang et al., 2016; Jagadeeswaran et al., 2010; Surridge et al., 2011; Zhang et al., 2013), indicating the presence of piRNAs. Piwi RNAs (piRNAs) are the class of small RNAs mediating chromatin modifications (Ross, Weiner, & Lin, 2014) which are derived mainly from retrotransposons and other repetitive elements with high sequence diversity (Ross et al., 2014; Siomi, Sato, Pezic, & Aravin, 2011; Zhang et al., 2013). Thus, our results indicated that T. tabaci genome not only harbors miRNAs but also other small RNAs such as piRNAs that might be involved in the transgenerational epigenetic inheritance (Weick & Miska, 2014).…”
Section: Discussionmentioning
confidence: 99%